ELECTROCATALYTIC DESTRUCTION OF PHENOL ON MANGANESE OXIDE (IV) DOPED BY IONS OF Fe2+ - Іванов, С.; Сокольський, Г.; Демченко, М.; Руденко, Г. (Proceedings of National Aviation University (archive), 2012)
An electrochemical method combines possibilities of direct anodal electrochemical oxidation, and also chemical destruction due to the generating anodal ions of suroxide. Possibility of electrocleaning of water solutions from a phenol with application of manganese dioxide electrode doped by ions of Fe2+ is analysed. Anodal oxidation of water solutions of C6H5OH is experimentally conducted with the use of electrodes from stainless steel, platinum electrodes, and also by the manganese dioxide electrode doped by ions of Fe2+ . Manganese dioxide electrode appeared as the most active electro-catalyst: at the use of Pt to the anode has been destruсted 2,5 % of phenol, and at the use of MnO2 doped by the ions of Fe2+- 64,6 %. Stainless steelel ectrode wasn’t active at the process of phenol destruction in the conditions of experiment